(Re)situating Women in Irish Revolutionary History by (Re)Doing Undone Gender : A Critical Discourse Analysis of Sean O'Faolain's Biography "Constance Markievicz". - Woodlock,John (2014)
The production of knowledge and claims of objectivity in Irish revolutionary historical narratives are discursively gendered processes which maintain a power-differentiation between the sexes through the assignment of a hierarchy of significance to the participation of men and women in the Irish struggles for independence. The partial visibility of women in such historical accounts is discursively maintained by the masculinization of Irish historical knowledge production where nationalist revolutionary discourses have been articulated by men as male-only spaces, preserving a hegemonic male-hero image. What happens to discourses of masculinity when leading women enter the realm of revolution? Do women, through active and prominent participation, threaten the stability of such narratives and of the discursively constructed social orders that are maintained by the privilege and power to define how history will remember who qualifies as a hero and who does not? The gendered selectivity of historical memory is often articulated through rhetorical applications of specific language manifestations which subordinate the participation of women in revolutionary narratives to the participation of men. The legacy of Constance Markievicz suffers from this biased form of knowledge production where a discursive gendered historical inheritance has tainted her common image in Irish history and social memory.
Keywords: patriarchy; objectivity; participation; allegory; visibility